Factor motivate company to use global sourcing / Hazwani Darus - Darus, Hazwani (Faculty of Business and Management, 2010)
Global sourcing is promoted as one of the most powerful trends in modern management. The rationale for global sourcing some functions and processes includes achieve world-class quality, flexible global resource pool, and low risk. This research investigates various benefits that firms perceive in global sourcing. Data were collected from 50 companies in Melaka Tengah, Melaka. Three motivation factor of using global sourcing were identified. The types and levels of benefits factors a firm achieved from global sourcing were significantly different in various terms. Information provided by this study expands our understanding of sourcing activities by others company. From finding, the researcher found that the company satisfy with the global sourcing activity that their company done. They will use global sourcing in their organization in future. The most important reason to use global sourcing because has flexible global resource pool.